Partnering with patients in quality improvement: towards renewed practices for healthcare organization managers? - Nathalie Clavel; Marie-Pascale Pomey; Djahanchah Philip (Sacha) (BMC, 2019)
Abstract Background Around the world, many healthcare organizations engage patients as a quality improvement strategy. In Canada, the University of Montreal has developed a model which consists in partnering with patient advisors, providers, and managers in quality improvement. This model was introduced through its Partners in Care Programs tested with several quality improvement teams in Quebec, Canada. Partnering with patients in quality improvement brings about new challenges for healthcare managers. This model is recent, and little is known about how managers contribute to implementing and sustaining it using key practices. Methods In-depth multi-level case studies were conducted within two healthcare organizations which have implemented a Partners in Care Program in quality improvement. The longitudinal design of this research enabled us to monitor the implementation of patient partnership initiatives from 2015 to 2017. In total, 38 interviews were carried out with managers at different levels (top-level, mid-level, and front-line) involved in the implementation of Partners in Care Programs. Additionally, seven focus groups were conducted with patients and providers. Results Our findings show that managers are engaged in four main types of practices: 1-designing the patient partnership approach so that it makes sense to the entire organization; 2-structuring patient partnership to support its deployment and sustainability; 3-managing patient advisor integration in quality improvement to avoid tokenistic involvement; 4-evaluating patient advisor integration to support continuous improvement. Designing and structuring patient partnership are based on typical management practices used to implement change initiatives in healthcare organizations, whereas managing and evaluating patient advisor integration require new daily practices from managers. Our results reveal that managers at all levels, from top to front-line, are concerned with the implementation of patient partnership in quality improvement. Conclusion This research adds empirical support to the evidence regarding daily managerial practices used for implementing patient partnership initiatives in quality improvement and contributes to guiding healthcare organizations and managers when integrating such approaches.